2022
DOI: 10.1186/s42047-022-00106-w
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative hematological inflammatory markers associated with grade and survival in Meningiomas

Abstract: Meningiomas represent the most frequently diagnosed intracranial tumors. Inflammatory cells present in the tumor can modulate both antitumor and protumor functions, and modify the therapeutic response. Hematological inflammatory parameters have provided prognostic information useful in the treatment and clinical evaluation of several tumors. The aim of this study was to evaluate preoperative hematological markers of patients with meningiomas and to relate them to clinical variables and recurrence-regrowth free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…After several stages of eligibility screening, a total of six studies were included in this study. [ 5 , 12 , 21 , 24 , 25 , 30 ] All collected studies describe hematological inflammatory markers and the association of the pathological grade of meningioma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After several stages of eligibility screening, a total of six studies were included in this study. [ 5 , 12 , 21 , 24 , 25 , 30 ] All collected studies describe hematological inflammatory markers and the association of the pathological grade of meningioma.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our study, NLR, MLR, and LMR have a role in predicting meningioma grade. [24] Retrospective [21] Retrospective Y Y Y U U U U U U U Y 4/11 (36.36) High Silva et al (2022) [5] Retrospective U Y Y U U U U Y U U Y 4/11 (36.36) High Manjunath et al (2022) [30] Retrospective U Y Y U U U U U U U Y 3/11 (27.27) High Guidry et al (2023) [12] Retrospective U e quality assessment of the included studies varied, with most studies categorized as having a moderate or low risk of bias. In addition, heterogeneity between studies was observed in some analyses, which may be due to differences in patient characteristics and measurement methods.…”
Section: Discussionmentioning
confidence: 99%